1998
DOI: 10.1074/jbc.273.51.34022
|View full text |Cite
|
Sign up to set email alerts
|

Contributions to Maxima in Protein Kinase C Activation

Abstract: In many lipid systems, the activity of protein kinase C (PKC) exhibits a peak followed by a decline as the mol % of one component is increased. In these systems, an increase in one lipid component is always at the expense of another or accompanied by a change in total lipid concentration. Here we report that in saturated phosphatidylserine (PS)/phosphatidylcholine (PC)/diacylglycerol (DAG) mixtures, increasing PS or DAG at the expense of PC revealed an optimal mol % PS, dependent on mol % DAG, with higher mol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 50 publications
5
25
1
Order By: Relevance
“…These authors proposed that the decreased activity observed at high lipid concentrations was due to the dilution of PKC dimers or higher aggregates with greater kinase activity. However, in contrast to the present study, the decrease in PKC activity was associated with a decreased autophosphorylation (54). of CDCA in the absence or presence of 5 g PS.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…These authors proposed that the decreased activity observed at high lipid concentrations was due to the dilution of PKC dimers or higher aggregates with greater kinase activity. However, in contrast to the present study, the decrease in PKC activity was associated with a decreased autophosphorylation (54). of CDCA in the absence or presence of 5 g PS.…”
Section: Discussioncontrasting
confidence: 54%
“…This latter observation could explain, at least in part, the results in the present study that the increased phosphorylation of PKC␣ by CDCA, although not leading to a direct activation of this kinase, increases the affinity and, in turn, the activation of PKC␣ by PMA. Sando et al (54) have observed a correlation between autophosphorylation and activation of PKC with a lipid-dependent, normally distributed activation pattern. These authors proposed that the decreased activity observed at high lipid concentrations was due to the dilution of PKC dimers or higher aggregates with greater kinase activity.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with a concentration-dependent equilibrium between monomeric and dimeric forms of PKC␣. Evidence supporting the notion that PKC may be active in PKC-PKC and/or PKC-substrate complexes has also been provided elsewhere (55)(56)(57)(58)(59)(60). Furthermore, evidence that PKC may become active upon self-association in the cellular environment was presented recently based on the observation of PKC␣ dimers in lysates derived from murine B82L fibroblasts treated with calcium ionophore, phorbol ester, or epidermal growth factor (60).…”
Section: Discussionmentioning
confidence: 83%
“…ingenol 3-angelate could not cause the same degree of association of the C1b domain with lipid that is induced by DAG or PMA. The basis of the decrease in association of the C1b domain at high ligand concentrations is uncertain, but optimal concentrations of different activators for maximal activation have been reported previously (52,53), suggesting submaximal effects at higher ligand concentrations. It clearly does not appear to reflect a major change in the composition of the bulk lipid phase, because the incorporation of the ligand into the liposome in the absence of receptor was modest (see Fig.…”
Section: Resultsmentioning
confidence: 99%